Situational Analysis of Labour Turn Out in the Ghanaian Education Sector: The Strides and Preferences - Amoah, Samuel Asare (International Journal of Asian Social Science, 2019)
The purpose of the study was to do a situational analysis of teacher turn-out in the Ghanaian education sector. Using a descriptive survey design the study considered the population of education experts including directors, circuit supervisors and the headteachers and teachers of basic education sector. A sample size of 45 respondents, selected through the use of homogenous, purposive, and stratification, sampling techniques. Data were collected with the help of a self-developed questionnaire and interview guide. The information collected was analysed using frequencies and thematic approach. Some push factors include teachers’ likeness of the environment, teachers are satisfied with effort within the educational environment. In addition the ease of getting assurances and transfers are the common form of recruitment procedure for the teachers. Also teachers retention and participants characteristics, teacher’s ability to manage the variety of observations and attitudes of people within an environment as well as learning from different types of ideas in a collaborative reflective environment came out strongly as some of the findings. It is concluded and recommended that varied structural factors influenced labor turn out in education sector, effective in-service training is needed to train mentors in the municipality such that teacher can be given effective counselling and mentorship training, reflective collaborative activities need to be encouraged so that teachers can interact with their colleagues in a more worthwhile activities that can promote their professional well-being in the municipality.